Neuroprotection in a Novel Mouse Model of Multiple Sclerosis - Lidster, Katie; Jackson, Samuel J.; Ahmed, Zubair; Munro, Peter; Coffey, Pete; Giovannoni, Gavin; Baker, Mark D.; Baker, David (PLOS ONE, 2013)
Multiple sclerosis is an immune-mediated, demyelinating and neurodegenerative disease that currently lacks any neuroprotective treatments. Innovative neuroprotective trial designs are required to hasten the translational process of drug development. An ideal target to monitor the efficacy of strategies aimed at treating multiple sclerosis is the visual system, which is the most accessible part of the human central nervous system. A novel C57BL/6 mouse line was generated that expressed transgenes for a myelin oligodendrocyte glycoprotein-specific T cell receptor and a retinal ganglion cell restricted-Thy1 promoter-controlled cyan fluorescent protein. This model develops spontaneous or induced optic neuritis, in the absence of paralytic disease normally associated with most rodent autoimmune models of multiple sclerosis. Demyelination and neurodegeneration could be monitored longitudinally in the living animal using electrophysiology, visual sensitivity, confocal scanning laser ophthalmoscopy and optical coherence tomography all of which are relevant to human trials. This model offers many advantages, from a 3Rs, economic and scientific perspective, over classical experimental autoimmune encephalomyelitis models that are associated with substantial suffering of animals. Optic neuritis in this model led to inflammatory damage of axons in the optic nerve and subsequent loss of retinal ganglion cells in the retina. This was inhibited by the systemic administration of a sodium channel blocker (oxcarbazepine) or intraocular treatment with siRNA targeting caspase-2. These novel approaches have relevance to the future treatment of neurodegeneration of MS, which has so far evaded treatment.